Atlas of woody plants in China distribution and climate - Fang, Jingyun; Wang, Zhiheng; Tang, Zhiyao (Springer eBooks., 2011)
"Atlas of Woody Plants in China: Distribution and Climate? documents the spatially-explicit county-level distribution of all 11,405 woody plants in China, together with life form information for most species. It also provides climate information for each species, with the county-level average and range of 12 climatic indices and of vegetation net primary productivity. It is the first and largest comprehensive atlas in the world for the distribution of China?s plants and was compiled on the basis of almost all related literature published throughout China. The atlas should serve as an indispensable handbook for all those who are interested in the plants, ecology, geography, environment, horticulture, and silviculture of China and East Asia. Dr. Jingyun Fang is a Cheung Kong Professor at the Department of Ecology, Peking University, China. Dr. Zhiheng Wang and Dr. Zhiyao Tang are both ecologists working at the same institute.